Teaching self-criticism and peer-critique skills to engineering students through a temporal survey-based program - Revilla-Cuesta, Víctor; Hurtado-Alonso, Nerea; Fontaneda, Ignacio; Skaf, Marta; Ortega-López, Vanesa (Frontiers in Education, 2024)
Introduction: Engineering students should develop critical-thinking skills and insist on appropriate performance levels both from themselves and from their colleagues during their training. In doing so, they will adopt critical attitudes towards their own and others' work. This will help them to successfully perform their future professional work with the highest standards. Methods: In this research, peer-and self-assessments of in-class presentations through a survey-based program were used to analyze the development of critical-thinking skills among engineering students. The program included two key features: firstly, formative assessments were repeatedly conducted over time; secondly, teachers' ratings were provided to students as comparative benchmarks. This approach encouraged students to reflect on their ratings over time using the reference of the teacher. Results: From a general perspective, the analysis of survey responses showed that students assigned lower ratings in assessments conducted at a later stage, despite receiving higher ratings from their teachers over time. Therefore, students became more demanding throughout the experience in spite of the increased quality of their work according to the teachers' assessments. Moreover, students tended to closely attune their evaluations to their teachers' ratings. Comparing peer-and self-assessments, it was noted that students were more demanding towards the work of their peers in the long term, and especially their ability to explain concepts, than they were towards their own work. Nevertheless, high temporary increases were observed in students' own self-assessments of presentation-file quality. Finally, students did not conduct overall evaluations with the same level of demand as their teachers at any time during the experience. Discussion: The results demonstrate that this program and similar initiatives are useful to help engineering students to develop critical-thinking skills and to broaden their expectations with respect to their own and their colleagues' work. However, other relevant aspects could be evaluated in lengthier programs, such as whether the students' levels of critical thinking and expectations are maintained when the comparative reference of a teacher's assessment is unavailable.